Pengaturan Mengenai Pengakuan Terhadap Organisasi Pemberontak Sebagai Subjek Hukum Ditinjau Dari Hukum Internasional - Rendyano Rizalno Hiariej; Arman Anwar; Welly Angela Riry (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Indonesia from time immemorial until after independence faced various kinds of problems, both international and non-international. Although this problem can be solved in different ways, there are also parties who can solve it in an unsympathetic way. This can encourage the emergence of conflicts arising from the current struggle, in particular armed conflicts.Purposes of the Research: This paper aims to examine and discuss how the regulation of rebel organizations as a legal subject is reviewed from international law.Methods of the Research: The method used is a normative juridical research method using a case approach, a statutory approach and a conceptual approach.Results of the Research: The results obtained from the study show that the instruments of international law governing rebels as subjects of international law are the Hague Convention IV of 1907, as well as The Supplementary Protocol II of the Geneva Conventions of 1949. The Rebels, Insurgents and Belligerents remain obliged to comply with the provisions of international law. The Free Papua Organization (OPM) does not yet have a juridical personality as a subject of international law because it does not meet the criteria for rebels as stipulated in the 1907 Hague Convention IV and the Geneva Conventions. 1949. While the status of the opening of the OPM Representative Office in the United Kingdom does not affect the British attitude in respecting the sovereignty and territorial integrity of Indonesia including the recognition of Papua as part of the Republic of Indonesia. The resolution of the Papuan conflict should take a way of peaceful and integrated negotiations with the interests of the welfare of the people in Papua as a whole.